A rare urogenital malformation “Herlyn-Werner-Wunderlich syndrome” (Ohvira syndrome) discovered during an acute pelvic pain - Kamal, E. Harcha; Ayoub, Aouragh; Ibtissam, Bellajdel; Hafssa, Taheri; Hanane, Saadi; Ahmed, Mimouni Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
The Herlyn-Werner-Wunderlich syndrome (OHVIRA syndrome) is a rare urogenital malformation, characterized by a blind hemivagina, a didelphic uterus, and homolateral renal agenesis, it results from a defect in the development of the muller and Wolf ducts during the embryonic period, of unknown origin, the diagnosis is most often made at puberty during the first menstruation, sometimes late, particularly for non-obstructive forms: infertility or obstetrical complications, the diagnosis is based on pelvic ultrasound especially with 3D reconstructions and pelvic magnetic resonance imaging (MRI) which remains the standard gold for the detection of mullerian anomalies, laparoscopy can also play a double diagnostic and prognostic role in order to study the consequences of the blood reflection (hematosalpinx, inflammatory pelvis, endometriosis. In this work we report the case of an OHVIRA syndrome diagnosed late at the age of 36 years in a multiparous woman with acute pelvic pain simulating the picture of a torsion of the adnexa, we will discuss through this case the clinical, diagnostic and therapeutic aspects of this uterine malformation.